Spirometric reference values for Malagasy adults aged 18–73 years - Ratomaharo, Julia; Linares Perdomo, Olinto; Collingridge, Dave S.; Andriamihaja, Rabezanahary; Hegewald, Matthew; Jensen, Robert L.; Hankinson, John; Morris, Alan H. (The European respiratory journal, 2015)
The American Thoracic Society (ATS) and European Respiratory Society (ERS) recommend that spirometry prediction equations be derived from samples of similar race/ethnicity. Malagasy prediction equations do not exist. The objectives of this study were to establish prediction equations for healthy Malagasy adults, and then compare Malagasy measurements with published prediction equations. We enrolled 2491 healthy Malagasy subjects aged 18–73 years (1428 males) from June 2006 to April 2008. The subjects attempted to meet the ATS/ERS 2005 guidelines when performing forced expiratory spirograms. We compared Malagasy measurements of forced expiratory volume in 1 s (FEV 1 ), forced vital capacity (FVC) and FEV 1 /FVC with predictions from the European Community for Steel and Coal (ECSC), the third National Health and Nutrition Examination Survey (NHANES III) and the ERS Global Lung Function Initiative (GLI) 2012 study. A linear model for the entire population, using age and height as independent variables, best predicted all spirometry parameters for sea level and highland subjects. FEV 1 , FVC and FEV 1 /FVC were most accurately predicted by NHANES III African-American male and female, and by GLI 2012 black male and black and South East Asian female equations. ECSC-predicted FEV 1 , FVC and FEV 1 /FVC were poorly matched to Malagasy measurements. We provide the first spirometry reference equations for a healthy adult Malagasy population, and the first comparison of Malagasy population measurements with ECSC, NHANES III and GLI 2012 prediction equations.